2009
DOI: 10.1017/s1751731108003844
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbial fermentation of high- and low-forage diets in Rusitec, single-flow continuous-culture fermenters and sheep rumen

Abstract: Eight Rusitec and eight single-flow continuous-culture fermenters (SFCCF) were used to compare the ruminal fermentation of two diets composed of alfalfa hay and concentrate in proportions of 80 : 20 (F80) and 20 : 80 (F20). Results were validated with those obtained previously in sheep fed the same diets. Rusitec fermenters were fed once daily and SFCCF twice, but liquid dilution rates were similar in both types of fermenters. Mean values of pH over the 12 h postfeeding were higher ( P , 0.001) in Rusitec than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 29 publications
7
28
1
Order By: Relevance
“…(2004a,b), who reported greater pH values and lower VFA concentrations in the rumen of goats and sheep fed diets composed either of AH or of OLSUP. Differences between in vivo and continuous‐culture fermenters in pH and VFA concentrations can be due to the relative amounts of daily input of feed and saliva produced (Carro et al., 2008). As in this study, the amount of saliva infused was the same in all fermenters, the lower pH values found in AH‐fed fermenters in comparison with OLSUP were probably due to increased VFA production, which was 1.41 times greater for AH.…”
Section: Resultsmentioning
confidence: 99%
“…(2004a,b), who reported greater pH values and lower VFA concentrations in the rumen of goats and sheep fed diets composed either of AH or of OLSUP. Differences between in vivo and continuous‐culture fermenters in pH and VFA concentrations can be due to the relative amounts of daily input of feed and saliva produced (Carro et al., 2008). As in this study, the amount of saliva infused was the same in all fermenters, the lower pH values found in AH‐fed fermenters in comparison with OLSUP were probably due to increased VFA production, which was 1.41 times greater for AH.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, studies with CCF have recently shown that the average pH (Calsamiglia et al, 2002), the time during which pH values are suboptimal (Cerrato-Sánchez et al, 2008), and the extent of pH variation (Wales et al, 2004) are important factors influencing ruminal fermentation. In addition, the pH in the fermenters has been thought to be responsible for shifts in the rumen bacterial population (Yang et al, 2002;Calsamiglia et al, 2008;Carro et al, 2009). These findings underline the need to maintain in vitro pH values across time that are as close as possible to those in the rumen of animals consuming similar diets to sustain similar compositions and structures of microbial community and, thus, to accurately simulate ruminal fermentation (Devant et al, 2001;Colombatto et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies (Hoover et al, 1976;Crawford et al, 1980;Carro et al, 2009;Muetzel et al, 2009) seem to indicate an effect of the feed-tobuffer ratio (F/B; g of DM feed/L of buffer) on the pH reached in CCF, and although this ratio has been proposed as being responsible for pH changes , to our knowledge, no studies have analyzed the effect of different F/B. Because many discrepancies in fermentation between rumens and CCF have been clearly attributed to differences in pH values (Mansfield et al, 1995;Molina-Alcaide et al, 2009), the F/B should be carefully chosen in fermenters in which pH is not under control.…”
Section: Introductionmentioning
confidence: 99%
“…Okamoto () reported that when sheep were fed hay and barley, the concentration of total VFA in the rumen was reached a maximum 3 h after feeding and it decreased slowly until 12 h after feeding. In other studies, in ruminant fed a forage‐based diet, the total VFA reached a maximum value after 1.5–4 h (Sutoh et al ; Carro et al ; Zhang et al ). The BHBA, which is converted from butyrate in the rumen epithelium, was higher between 2 and 3 h after feeding, or between 2 and 4 h in multiparous dairy cows (Blum et al ; Nikkhah et al ).…”
Section: Resultsmentioning
confidence: 84%